(untitled) (Al-Farooq Journal of Sciences, 2026)
Hyperbilirubinemia is one of the most common clinical disorders in newborns, requiring accurate laboratory diagnosis and early intervention to avoid serious neurological complications. This study aimed to evaluate the variation in bilirubin levels based on birth weight and analyze the relationship between Rh incompatibility and the need for blood transfusions in newborns. A cross-sectional study was conducted on a sample of 50 newborns. Clinical and laboratory data were collected and statistically analyzed using SPSS, employing the independent samples t-test and Fisher’s Exact Test. The t-test results showed strong and clinically significant differences in bilirubin levels attributable to birth weight (t = 4.583, p = 0.000), with infants weighing over 5 kg exhibiting higher mean bilirubin levels compared to other newborns. On the other hand, the frequency distribution showed that all blood transfusions were exclusively within the Rh-negative group (21.1%). However, Fisher’s exact test did not show a statistically significant correlation (p = 0.319) due to the limited sample size and the effectiveness of early therapeutic and preventive interventions. The study concludes that microsomal (large birth weight) is a significant indicator of elevated free bilirubin levels, requiring immediate and intensive laboratory monitoring. It also emphasizes the importance of coordinating immunological and physiological indicators to ensure a comprehensive treatment protocol for newborns.